A STUDY ON THE MAGNITUDE OF HUMAN RESOURCE IN SUN AND RANBAXY MERGER - S, Anjali Daisy; C, Vijaya Banu (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Sun Pharmaceutical is a trailblazer in Indian pharmaceutical sector, and one of the foremost competitors in the generic drug market sets its eye onRanbaxy. Sun pharmacy which was established in 1983 listed from 1994 has its upper hand in product development. Ranbaxy was incorporated in1973, and Daiichi Sankyo, a Japanese firm, got a controlling share from 2008. This amalgamation between Sun Pharmacy and Ranbaxy would get profitable transaction for the former. The process of the coalition was a cloak and dagger affair until April 6, 2014. Before mergers and acquisitions, a company has to create an urgency call among the employees which will result in better understanding of the whole scenario. The aspects are about how financial motives and non-financial motives play a major role in mergers. This case deals with the human resource issues and complexities faced by the two players in the same business. Keywords: Merger, Acquisition, Change management, Human resource, Employee engagement, Corporate strategy.